Preparation method and application of C and Cu co-doped low-temperature magnetic composite material

By co-doping the CuFe2O4 material with C and Cu, a low-temperature magnetic composite material C/Cu/CuFe2O4 with a particle size of micro-nanometers was prepared, which solved the problem of the existing materials' magnetic transition temperature being concentrated between 270 and 310K, and achieved the The magnetic transition temperature is between 99-110K, meeting the needs of magnetic refrigeration in the near-room temperature zone.

CN119419054APending Publication Date: 2025-02-11CHANGSHA DINGXIN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411588628.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The magnetic transition temperature of existing room temperature magnetic working fluid materials is concentrated between 270 and 310K, and there is a lack of low-temperature magnetic materials (100-200K) to meet the needs of magnetic refrigeration in the near-room temperature zone.

Method used

By co-doping the CuFe2O4 material with C and Cu, the concentration of Cu2+ ions in CuFe2O4 is changed, and the preparation route of combining hydrothermal method and solid phase method is used to prepare a low-temperature magnetic composite with a particle size of micro-nanometers and smooth surface. Material C/Cu/CuFe2O4.

Benefits of technology

The magnetic transition temperature of the magnetic composite material is achieved between 99-110K, filling the gap in low-temperature magnetic materials, and has great application prospects in the field of magnetic refrigeration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419054A_ABST
    Figure CN119419054A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a C and Cu co-doped low-temperature magnetic composite material. The preparation method specifically comprises the following steps: preparing a solution, carrying out hydrothermal reaction, carrying out suction filtration, drying to obtain an iron-based precursor, mixing and grinding the iron-based precursor with CuO, and calcining and grinding twice under the protection of an inert atmosphere to obtain the C / Cu / CuFe2O4 low-temperature magnetic composite material. Wherein in the preparation process, a protective atmosphere for calcining and an iron-based precursor containing carbon atoms are selected, so that a reducing atmosphere is favorably formed, the formation of metallic copper and carbon is guaranteed, and the preparation of the magnetic material C / Cu / CuFe2O4 is realized. The magnetic property of CuFe2O4 is changed on the basis of a heteroatom C and Cu doping method, the magnetic transition temperature of the magnetic composite material is 99-110 K, and the magnetic composite material has important significance in preparation of magnetic materials with low magnetic transition temperature, can be used as a near-room-temperature magnetic refrigeration working medium and has a great application prospect in the field of magnetic refrigeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrite magnetic materials, and in particular to a preparation method of a C and Cu co-doped low-temperature magnetic composite material and application thereof. Background Art

[0002] In order to solve the energy and environmental problems currently faced by mankind, magnetic refrigeration technology, as a new generation of refrigeration technology that is environmentally friendly, efficient and reliable, has attracted the attention of more and more researchers. Compared with the low efficiency of compressors in low-temperature refrigeration, in the application field of magnetic materials, magnetic refrigeration through its magnetocaloric effect is one of the important research directions at present. The magnetocaloric effect means that when the external magnetic field changes, the orderly arrangement of the magnetic moment of the magnetic material will change, that is, the magnetic entropy changes, which causes the magnetic material itself to absorb or release heat. Therefore, the new technology that uses this effect of magnetic materials to achieve refrigeration is called magnetic refrigeration. The basic principle of magnetic refrigeration includes that during the excitation process, the magnetic moment of the magnetic material changes from disorder to order along the direction of the magnetic field, the magnetic entropy decreases, and the magnetic working fluid releases heat to the outside; while during the demagnetization process, its magnetic moment changes from order to disorder along the direction of the magnetic field, the magnetic entropy increases, and the magnetic working fluid absorbs heat from the outside. In addition, under adiabatic conditions and during the excitation / demagnetization process, the magnetic working fluid has no heat exchange with the outside world, and the magnetic field does work on the material, causing the internal energy of the material to change, thereby changing the temperature of the material itself. Therefore, magnetocaloric working fluids with different magnetic transition temperatures are used to form active magnetic refrigeration cycles with coupled regenerative refrigeration in different refrigeration temperature zones. Working fluids in different axial positions are used to realize magnetic refrigeration cycles in respective temperature zones, thereby increasing the cycle temperature span, such as a medium- and low-temperature magnetic refrigeration cycle (temperature zone of 20-77K) coupled with pulse tube refrigeration. Although there are still problems in phase matching between the coupling of gas expansion effect and magnetocaloric effect, given that pulse tube refrigerators have the characteristics of no moving parts in the low temperature zone, low vibration, high reliability, and are widely used in cooling infrared detectors on spacecraft, exploring the research of magnetic working fluids in magnetic refrigeration cycles is still one of the important topics in this field [Journal of Central South University (Science and Technology), 2021, 52(6): 1757-1765.], and great progress has been made in coupled room temperature magnetic refrigeration prototypes [Journal of Engineering Thermophysics, 2013, 34, 5 (in Chinese); Acta Phys. Sin. 2017, 66(11), 110701.].

[0003] The key materials in magnetic refrigeration are mainly divided into three categories according to the temperature range, namely low temperature magnetic fluid (below 20K), medium temperature magnetic fluid (20-77K) and near room temperature magnetic fluid (above 77K). The current room temperature magnetic fluid materials are mainly Gd, Gd5Si2Ge2, LaFe 11.2 Co 0.7 Si 1.1 Most of them are based on rare earth elements and are expensive. In addition, the magnetic transition temperatures (Curie temperatures) of these current room-temperature magnetic materials are mainly concentrated in the range of 270-310K. There is still a gap in low-temperature magnetic materials (100-200K) in near-room-temperature magnetic materials.

[0004] Spinel ferrite is an important type of magnetic nanoparticles, with a general formula of AB2O4. Both the tetrahedral A site and the octahedral B site represent magnetism. CuFe2O4, as a typical spinel structure ferrite, has stable chemical properties, and its synthesis and use are non-toxic, cheap, easy to obtain, and recyclable. Therefore, it has attracted widespread attention in the application of sensors, electronics, especially catalysis, electrochemical energy storage, etc. At present, the magnetic material CuFe2O4 (KJKim, Journal of Magnetism and Magnetic Materials 279 (2004) 173-177) or Cu x -Cu (0.5-x) Zn 0.5 Fe2O (4-x) (Chinese patent, CN 113332988B) can be used not only in magneto-optical recording and high-frequency communication, but also as a catalyst for the catalytic conversion of aromatic aldehydes, cyanoacetonitrile and methylene (JKRajput, Ultrasonics Sonochemistry, 26 (2015) 229-240). The C / CuFe2O4 (S.Nilmoung, Journal of Alloys and Compounds 688 (2016) 1131-1140) and Cu-CuFe2O4 / G (Chinese patent, CN108400299 A) composite materials prepared based on spinel structure ferrite CuFe2O4 also show good electrochemical properties and great application potential in lithium ion battery and sodium ion battery negative electrode materials. It should be pointed out that in order to prepare the above-mentioned C / CuFe2O4 and Cu-CuFe2O4 / G composite materials, on the one hand, carbon nanofibers (C) and graphene need to be additionally introduced (such as Chinese patent CN 108400299 A), and on the other hand, CuFe2O4 or Cu-CuFe2O4 is loaded on the surface of carbon nanofibers (C) and graphene (G) or exists independently in the composite material.

[0005] In addition, CuFe2O4 composite materials have attracted extensive attention from researchers due to their special properties and application potential in magnetism, catalysts and energy storage, as well as changes in their crystal structure, which lead to changes in heat capacity and magnetic properties, forming magnetic heating effects, etc. In particular, compared with gas compression refrigeration (the efficiency is generally 20-40%), the theoretical efficiency of magnetic refrigeration can reach 60-70% of the Carnot cycle efficiency. Studies have shown that the Néel temperature of the magnetic transition of CuFe2O4 materials is generally T N = around 728-740K, and its transition temperature distribution range is relatively wide. However, at present, no research has reported its low-temperature magnetic properties (such as magnetic properties under 100-200K conditions). Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a method for preparing a C, Cu co-doped low-temperature magnetic composite material and its application, by doping CuFe2O4 material with heterogeneous atoms and changing Cu 2+ The concentration of ions in CuFe2O4 can not only utilize the presence of C atoms to improve the poor intrinsic conductivity of CuFe2O4 materials, but also utilize the possible coordination effect between ferrite and copper in magnetic properties to achieve its specific low-temperature magnetic properties. It has good application prospects in magnetic refrigeration, battery negative electrode materials, medical treatment, aerospace and other fields.

[0007] In order to achieve the above object, the present invention first provides a method for preparing a C and Cu co-doped low-temperature magnetic composite material, comprising the following steps:

[0008] S1. Dissolve iron salt and terephthalic acid (C8H6O4) in N,N-dimethylformamide (DMF), and mix them evenly by magnetic stirring to obtain a mixed solution;

[0009] S2, transferring the mixed solution obtained in S1 into a polytetrafluoroethylene tank, and sealing it in a stainless steel reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, the product is filtered, washed, and dried in a vacuum drying oven, and then ground to obtain an iron-based precursor;

[0010] S3, grinding the iron-based precursor obtained in S2, then adding copper oxide, and grinding and mixing the two to obtain a mixed powder;

[0011] S4, placing the mixed powder obtained in S3 into a tubular furnace, heating to 850°C-900°C under an inert atmosphere for 900-1200 min, cooling naturally to room temperature, and grinding the reaction product to obtain a C / Cu / CuFe2O4 intermediate;

[0012] S5. Grind the C / Cu / CuFe2O4 intermediate obtained in S4 again and place it in a tube furnace, heat it to 850℃-1000℃ in an inert atmosphere and react for 1440-1800min, and cool it to room temperature in the furnace to obtain C / Cu / CuFe2O4, a C and Cu co-doped low-temperature magnetic composite material. Grind again to mix the components evenly and further refine them.

[0013] Preferably, the iron salt in step S1 is any one or both of FeCl3·6H2O and Fe(NO3)3·9H2O.

[0014] Preferably, the molar ratio of the iron salt to terephthalic acid in step S1 is 1:1.5-2.

[0015] Preferably, in step S2, the hydrothermal reaction temperature is 150° C.-200° C., and the hydrothermal reaction time is 900-1200 min.

[0016] Preferably, in step S2, the drying temperature is 80-100° C., and the drying time is 900-1200 min.

[0017] Preferably, in step S3, after the iron-based precursor is mixed with copper oxide, the molar ratio of copper atoms to iron atoms is 1:1 to 1.1.

[0018] Preferably, the inert atmosphere in steps S4 and S5 is one of argon or nitrogen.

[0019] Based on a general inventive concept, the present invention also provides an application of a low-temperature magnetic composite material in magnetic refrigeration or a negative electrode material for a lithium / sodium battery, characterized in that, in the application of magnetic refrigeration, the low-temperature magnetic composite material is used as a magnetic working fluid.

[0020] The present invention combines a hydrothermal method with a solid phase method to prepare a low-temperature composite magnetic material C / Cu / CuFe2O4. First, a solution of iron salt and terephthalic acid is prepared in a stoichiometric ratio, and then an iron-based precursor is prepared under hydrothermal conditions. When preparing the iron-based precursor, the morphology of the iron-based precursor is regulated by controlling the amount of the ligand (terephthalic acid) added to prepare the iron-based precursor and its hydrothermal reaction temperature. Then, after the iron-based precursor and copper oxide are mixed in a stoichiometric ratio, they are sintered in an inert gas atmosphere, which is conducive to forming a reducing atmosphere, thereby forming metallic copper (Cu 0 ) and carbon phase (C) to achieve C, Cu (Cu 0) doping. The setting of the temperature range of two grindings and two calcinations is conducive to the uniform mixing of the components and the stability and uniformity of the physical and chemical properties of the final product. The calcination temperature range is set to 850℃-900℃ or 850℃-1000℃, which can ensure that the prepared samples contain CuFe2O4 components with spinel structure. The components of the prepared magnetic material are controlled by designing the reaction atmosphere and calcination temperature to achieve the preparation of multi-component C / Cu / CuFe2O4 composite materials.

[0021] The above scheme of the present invention has the following beneficial effects:

[0022] 1. Through heterogeneous atoms C, Cu (Cu 0 ) co-doping changes the Cu occupying octahedral position in the crystal structure of CuFe2O4 2+ The concentration of CuFe2O4 is changed by the method of heterogeneous atoms C and Cu doping to change its magnetic properties. Through hydrothermal reaction and secondary solid phase reaction under argon protective atmosphere, a magnetic composite material C / Cu / CuFe2O4 with micro-nano particle size and smooth surface is obtained. The magnetic properties of CuFe2O4 are changed by the method of heterogeneous atoms C and Cu doping. The magnetic transition temperature of the magnetic composite material is 99-110K, which is of great significance for the preparation of magnetic materials with low magnetic transition temperature. It can be used as a near-room temperature magnetic refrigeration working fluid and has great application prospects in the field of magnetic refrigeration.

[0023] 2. The present invention adopts a preparation route combining a hydrothermal method and a solid phase method, which has the characteristics of simple synthesis process, low cost and high stability of the synthetic product. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a SEM image of the C / Cu / CuFe2O4 composite material obtained in Example 1 of the present invention;

[0026] Figure 2 This is the XRD pattern of the C / Cu / CuFe2O4 composite material obtained in Example 1 of the present invention;

[0027] Figure 3 The low temperature magnetic properties of the C / Cu / CuFe2O4 composite material obtained in Example 1 of the present invention are as follows: Figure 3(a) is the curve of the relationship between the magnetic moment of the sample and the temperature change in the temperature range of 4-300K when the external magnetic field is 500Oe under zero field cooling; Figure 3 (b) is the first derivative curve of the MT curve;

[0028] Figure 4 This is an EDS graph of the C / Cu / CuFe2O4 composite material obtained in Example 1 of the present invention, wherein Cu:Fe=1:1. This graph shows that the atomic ratio of metal atoms in the prepared C / Cu / CuFe2O4 composite material is Cu:Fe=1:1.

[0029] Figure 5 This is a SEM image of the C / Cu / CuFe2O4 composite material obtained in Example 2 of the present invention;

[0030] Figure 6 This is the XRD pattern of the C / Cu / CuFe2O4 composite material obtained in Example 2 of the present invention;

[0031] Figure 7 The low temperature magnetic properties of the C / Cu / CuFe2O4 composite material obtained in Example 2 of the present invention; wherein Figure 7 (a) is the curve of the relationship between the magnetic moment of the sample and the temperature change in the temperature range of 4-300K when the external magnetic field is 500Oe under zero field cooling; Figure 7 (b) is the first-order derivative curve of the MT curve. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0033] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0034] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art; unless otherwise specified, the reagents used in the examples are commercially available.

[0035] Example 1

[0036] The preparation of C / Cu / CuFe2O4 magnetic material comprises the following steps:

[0037] (1) Iron salt (FeCl3·6H2O) and terephthalic acid (C8H6O4) were weighed in a molar ratio of 1:1.5, dissolved in N,N-dimethylformamide (DMF), and magnetically stirred for 10 min to mix well.

[0038] (2) The mixed solution obtained in (1) was transferred into a polytetrafluoroethylene tank, and sealed in a stainless steel reactor, and then placed in an electric heated air drying oven for reaction at 150°C for 900 min. After the reaction was completed, the mixture was naturally cooled to room temperature, the product was filtered, and then placed in a vacuum drying oven for heat preservation at 80°C for 900 min.

[0039] (3) The product obtained in (2) was ground for 45 minutes and then weighed. Copper oxide (CuO) was weighed according to the stoichiometric ratio (Fe:Cu atomic ratio 1:1), and the two were ground for 90 minutes to mix evenly.

[0040] (4) The product obtained in (3) was placed in a tubular furnace and kept at 850° C. for 900 min under an argon atmosphere. After naturally cooling to room temperature, the reaction product was ground for 45 min.

[0041] (5) The product obtained in (4) was ground again for 30 min and placed in a tubular furnace for reaction at 950 °C for 1440 min under an argon atmosphere. The product was cooled to room temperature to obtain C / Cu / CuFe2O4 magnetic material.

[0042] The C / Cu / CuFe2O4 magnetic material prepared above was tested and characterized. The results are as follows Figures 1 to 4 shown.

[0043] Figure 1 This is the SEM image of the C / Cu / CuFe2O4 composite material of this embodiment. Figure 1 It shows that the particle size of the prepared samples is micro-nanoscale. Figure 2 This is the XRD diagram of the C / Cu / CuFe2O4 composite material of this embodiment. The XRD diagram confirms that the prepared product contains three components of C, Cu, and CuFe2O4 at the same time. The C / Cu / CuFe2O4 composite material is obtained by changing the magnetic properties of CuFe2O4 by doping with heterogeneous atoms C and Cu.

[0044] Figure 3 The low temperature magnetic properties of the C / Cu / CuFe2O4 composite material obtained in this example. Figure 3 (a) is the curve of the relationship between the magnetic moment of the sample and the temperature change in the temperature range of 4-300K when the external magnetic field is 500Oe under zero field cooling; Figure 3 (b) is the first-order derivative curve of the MT curve. Figure 3 It shows that the magnetic transition temperature of the prepared C / Cu / CuFe2O4 composite material is 99K, which is significantly lower than the magnetic transition temperature of CuFe2O4 (728-740K).

[0045] Figure 4This is the EDS graph of the C / Cu / CuFe2O4 composite material of this embodiment. This graph shows that the atomic ratio of metal atoms in the prepared C / Cu / CuFe2O4 composite material is about Cu:Fe=1:1.

[0046] Example 2

[0047] The preparation of C / Cu / CuFe2O4 magnetic material comprises the following steps:

[0048] (1) The iron source (Fe(NO3)3·9H2O) and terephthalic acid (C8H6O4) were weighed in a molar ratio of 1:2.0, the iron salt and terephthalic acid were dissolved in N,N-dimethylformamide (DMF), and magnetically stirred for 10 min to mix well.

[0049] (2) The mixed solution obtained in (1) was transferred into a polytetrafluoroethylene tank, and sealed in a stainless steel reactor, and then placed in an electric heated air drying oven for reaction at 180°C for 900 min. After the reaction was completed, the mixture was naturally cooled to room temperature, the product was filtered, and then placed in a vacuum drying oven for heat preservation at 80°C for 900 min.

[0050] (3) The product obtained in (2) was ground for 45 minutes and then weighed. Copper oxide (CuO) was weighed according to the stoichiometric ratio (Fe:Cu atomic ratio 1:1), and the two were ground for 90 minutes to mix evenly.

[0051] (4) The product obtained in (3) was placed in a tubular furnace and kept at 850° C. for 900 min under an argon atmosphere. After naturally cooling to room temperature, the reaction product was ground for 45 min.

[0052] (5) The product obtained in (4) was placed in a tubular furnace and reacted at 950° C. for 1440 min under an argon atmosphere. The final experimental sample was obtained by cooling the furnace to room temperature.

[0053] The C / Cu / CuFe2O4 magnetic material prepared above was tested and characterized. The results are as follows Figures 5 to 7 shown.

[0054] Figure 5 This is a SEM image of the C / Cu / CuFe2O4 composite material obtained in this example. The particle size of the sample prepared in this example is also micro-nano scale.

[0055] Figure 6 This is the XRD diagram of the C / Cu / CuFe2O4 composite material obtained in this example, which also shows that the sample prepared in this example contains three components: C, Cu, and CuFe2O4.

[0056] Figure 7The low temperature magnetic properties of the C / Cu / CuFe2O4 composite material obtained in this example. Figure 7 (a) is the curve of the relationship between the magnetic moment of the sample and the temperature change in the temperature range of 4-300K when the external magnetic field is 500Oe under zero field cooling; Figure 7 (b) is a first-order derivative curve of the MT curve; the figure shows that the magnetic transition temperature of the C / Cu / CuFe2O4 composite material prepared in this example is 110K.

[0057] In summary, the present invention uses heterogeneous atoms C, Cu (Cu 0 ) co-doping changes the Cu occupying octahedral position in the crystal structure of CuFe2O4 2+ The concentration of CuFe2O4 is changed by the method of heterogeneous atoms C and Cu doping to change its magnetic properties. Through hydrothermal reaction and secondary solid phase reaction under argon protective atmosphere, a magnetic composite material C / Cu / CuFe2O4 with micro-nano particle size and smooth surface is obtained. The magnetic properties of CuFe2O4 are changed by the method of heterogeneous atoms C and Cu doping. The magnetic transition temperature of the magnetic composite material is 99-110K, which is of great significance for the preparation of magnetic materials with low magnetic transition temperature. It can be used as a near-room temperature magnetic refrigeration medium and has great application prospects in the field of magnetic refrigeration.

[0058] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a C and Cu co-doped low-temperature magnetic composite material, characterized in that: The following steps are involved: S1, dissolving iron salt and terephthalic acid in N,N-dimethylformamide, and mixing them evenly with magnetic stirring to obtain a mixed solution; S2, transferring the mixed solution obtained in S1 into a polytetrafluoroethylene tank, and sealing it in a stainless steel reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, the product is filtered, washed, and dried in a vacuum drying oven, and then ground to obtain an iron-based precursor; S3, grinding the iron-based precursor obtained in S2, then adding copper oxide, and grinding and mixing the two to obtain a mixed powder; S4, placing the mixed powder obtained in S3 into a tubular furnace, heating to 850°C-900°C under an inert atmosphere and keeping the temperature for 900-1200 min, cooling naturally to room temperature, and grinding the reaction product to obtain a C / Cu / CuFe2O4 intermediate; S5. Grind the C / Cu / CuFe2O4 intermediate obtained in S4 again and place it in a tubular furnace, heat it to 850℃-1000℃ under an inert atmosphere and react for 1440~1800min, then cool it to room temperature in the furnace to obtain C, Cu co-doped low-temperature magnetic composite material C / Cu / CuFe2O4.

2. The preparation method according to claim 1, characterized in that: In step S1, the iron salt is any one or two of FeCl3·6H2O and Fe(NO3)3·9H2O.

3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the iron salt to terephthalic acid is 1:1.5-2.

4. The preparation method according to claim 1, characterized in that: In step S2, the hydrothermal reaction temperature is 150° C.-200° C., and the hydrothermal reaction time is 900-1200 min.

5. The preparation method according to claim 1, characterized in that: In step S2, the drying temperature is 80-100° C., and the drying time is 900-1200 min.

6. The preparation method according to claim 1, characterized in that: In the step S3, after the iron-based precursor is mixed with copper oxide, the molar ratio of copper atoms to iron atoms is 1:1 to 1.

1.

7. The preparation method according to claim 1, characterized in that: The inert atmosphere in steps S4 and S5 is one of argon and nitrogen.

8. An application of a low-temperature magnetic composite material obtained by the preparation method according to any one of claims 1 to 7 in magnetic refrigeration or negative electrode materials for lithium / sodium batteries, characterized in that: In magnetic refrigeration applications, the low-temperature magnetic composite material is used as a magnetic working medium.

Citation Information

Patent Citations

  • Preparation method of CuFe2O4 / C composite negative electrode material used for sodium ion battery

    CN108400299A

  • A porous, magnetically conductive, self-doped copper-zinc ferrite catalyst, its preparation method, and its application.

    CN113332988B